Negative life events and college students’ adjustment: the mediating role of self-esteem and the moderating role of grade - Quan, Xiaoshan; Sun, Ji (Frontiers in Psychology, 2024)
The present research explored the relationship among negative life events, self-esteem, grade, and adjustment of college students. In total, 1,717 college students were investigated by the adolescent life events scale, Rosenberg self-esteem inventory, and Chinese college students' adjustment scale.The results showed that negative life events were negatively correlated with self-esteem and college students' adjustment. Moreover, self-esteem was positively correlated with college students' adjustment. Negative life events significantly negatively predicted college students' adjustment, and self-esteem mediated the relationship between negative life events and college students' adjustment.Grade moderated the effects of negative life events on college students' adjustment. These findings have broad implications for college students' mental health.